2020
DOI: 10.14202/vetworld.2020.812-820
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ethanolic Curcuma longa extract as a treatment for sand tampan ticks in a rabbit model

Abstract: Background and Aim: The soft tick Ornithodoros savignyi is distributed throughout Africa, including Egypt. It primarily attacks camels, cattle, donkeys, and cows; and rarely affects humans. This study evaluated the acaricidal efficacy of ethanolic Curcuma longa extract (Turmeric) on the second nymphs of O. savignyi and then investigated the safety of this herb in rabbits. Materials and Methods: The nymphs were immersed in 10, 5, 2.5, 1.25, and 0.625 mg/ml ethanolic C. longa extract. An additional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
1
0
3
Order By: Relevance
“…La alta movilidad de sustancias orgánicas desde el material vegetal no solo repercute en el rendimiento y la velocidad de extracción, sino, además, sobre la variedad de compuestos químicos presentes en el extracto con numerosas actividades biológicas, incluidas las toxicológicas [35], [36], [37]. Desde esta perspectiva, es probable que la formulación Curcuvet, igual que otros extractos hidroalcohólicos de C. longa [12], contenga altas concentraciones y variedad de compuestos potencialmente irritantes para la mucosa, lo cual explicaría la gravedad de las lesiones oftalmológicas observadas en este estudio.…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…La alta movilidad de sustancias orgánicas desde el material vegetal no solo repercute en el rendimiento y la velocidad de extracción, sino, además, sobre la variedad de compuestos químicos presentes en el extracto con numerosas actividades biológicas, incluidas las toxicológicas [35], [36], [37]. Desde esta perspectiva, es probable que la formulación Curcuvet, igual que otros extractos hidroalcohólicos de C. longa [12], contenga altas concentraciones y variedad de compuestos potencialmente irritantes para la mucosa, lo cual explicaría la gravedad de las lesiones oftalmológicas observadas en este estudio.…”
Section: Resultados Y Discusiónunclassified
“…El atractivo de esta planta como ingrediente farmacéutico activo tiene su origen en su demostrada actividad antioxidante, hepatoprotector, antiparasitaria externa, antiviral, antineoplásica, antinflamatoria, inmunomoduladora [12], [13], [14], [15], [16] y antimicrobiana [17], [18], [19], incluso frente a cepas patógenas portadoras de genes de resistencia a antibióticos [20]. Este último comportamiento se debe a su habilidad para dañar el ADN y la membrana microbiana, lo cual provoca la pérdida de los constituyentes citoplasmáticos, inactivación de importantes enzimas y desnaturalización de proteínas [14].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…A natural compound for combination therapy should be potent, but also less toxic toward normal cells (Yan et al, 2017). Previous acute and chronic toxicity studies showed that CL and PN are not toxic in animals (de Queiroz et al, 2013;Abdel-Shafy et al, 2020). Further, the study was continued using CL-PN combination to investigate the synergistic effect mechanism of combination thereof.…”
Section: Discussionmentioning
confidence: 99%
“…Such high percentages of curcumene has only been found in the genus Senecio (Asteraceae) [39]. Curcumene as major compound of EOs has been reported as larvicide against two-spotted spider mite, Tetranychus urticae [40] and in sand fly tick, Ornithodoros savignyi [41]. Shyobunol was the major constituent of the EO Lm ; the compound has been reported as an important element of the essential oil of Schinus molle leaves in Mexico and Tunisia [42], but is not a common major component in plant derivatives.…”
Section: Discussionmentioning
confidence: 99%